2020
DOI: 10.1371/journal.pone.0240528
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of emergency care delays experienced by traumatic brain injury patients presenting to a regional referral hospital in a low-income country

Abstract: Background Trauma is a leading cause of death and disability worldwide. In low-and middle-income countries (LMICs), trauma patients have a higher risk of experiencing delays to care due to limited hospital resources and difficulties in reaching a health facility. Reducing delays to care is an effective method for improving trauma outcomes. However, few studies have investigated the variety of care delays experienced by trauma patients in LMICs. The objective of this study was to describe the prevalence of pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 58 publications
(77 reference statements)
0
16
0
Order By: Relevance
“…A report from Tanzania in 2020 found that 95% of all severely injured patients needed but did not receive a brain CT scan. A majority (80.8%) of these patients also needed but did not receive oxygen [ 140 ]. Up to 60% of neurosurgeons managing pediatric neurotrauma reported needing a drill for pediatric neurosurgery [ 92 ].…”
Section: Search Resultsmentioning
confidence: 99%
“…A report from Tanzania in 2020 found that 95% of all severely injured patients needed but did not receive a brain CT scan. A majority (80.8%) of these patients also needed but did not receive oxygen [ 140 ]. Up to 60% of neurosurgeons managing pediatric neurotrauma reported needing a drill for pediatric neurosurgery [ 92 ].…”
Section: Search Resultsmentioning
confidence: 99%
“…Another factor in the large difference in mean delay is the poor road network in the more rural aspects of Southern Punjab, which sometimes only allow access for motorbikes or powerful off-road cars. 29 These are both issues that should be investigated and addressed by policy-makers, as even small delays to presentation have been associated with worsened prognoses 30 and significant emphasis in the trauma literature regarding the concept of the "Golden Hour," which indicates that prompt medical and surgical treatment in the initial stages of a traumatic injury can greatly reduce the risk of death. 31 Another interesting aspect of our study was that we found no evidence of adequate prehospital care in patients, as defined by ATLS or American College of Surgeons guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Greater acceptability and buy-in of this mechanism by neurosurgical providers are afforded by strategic purchasing because the costing and payment schedules are negotiated and prearranged in collaboration with the providers themselves. The payments from SHIs to neurosurgical providers can be further complemented by an element of pay-for-performance (32), with a proportion of the fixed payment withheld and paid according to certain indicators such as timeliness of the surgical operation (46), long-term outcomes assessment (47), and even patient satisfaction with the neurosurgeon-patient engagement (48). In this way, the goal of quality care can be achieved for the neurosurgical management of patients with TBI.…”
Section: Supply-side Financing: Strategic Purchasing Of Neurosurgical Servicesmentioning
confidence: 99%